GAMBARAN CT SCAN PADA PENDERITA PERDARAHAN SUBDURAL DI RSUP PROF. Dr. R. D KANDOU MANADO PERIODE JANUARI 2011- OKTOBER 2014 - Lonto, Aaron K. U.; Loho, Elvie; Mamesah, Yovana P. M.; Timban, Joan F. J. (e-CliniC, 2015)
Abstract: Subdural hemorrhage (SDH) is the most common form of intracranial lesions, approximately one-third of the incidence of severe head injury. However, it has been reported that about one-fifth of patients suffering subdural hemorrhage and other intracranial hemorrhage died undiagnosed.3 Examination computed tomography (CT) scan is the primary modality of choice when there is a suspected post-traumatic lesions. The purpose of research to know and study the SDH CT scan image. This study was a retrospective study conducted in the month of September to December 2014. The data were obtained through medical records and found 30 cases included in the study criteria. Overall the results, SDH more in male patients 27 people (90%). The largest age group in children (<12 years) 11 people (37%). Location SDH highest in the temporal 9 cases (30%).Keywords: subdural hemorhage, computed tomography scanAbstrak: Perdarahan subdural (PSD) adalah bentuk yang paling sering terjadi pada lesi intrakranial, kira-kira sepertiga dari kejadian cedera kepala berat. Namun, telah dilaporkan bahwa sekitar satu perlima dari penderita-penderita perdarahan subdural dan perdarahan intrakranial lainnya meninggal tidak terdiagnosis.3 Pemeriksaan computed tomography (CT) scan adalah modalitas pilihan utama bila diduga terdapat suatu lesi pasca trauma. Tujuan penelitian untuk mengetahui dan mempelajari gambaran CT scan PSD. Penelitian ini merupakan studi retrospektif yang dilakukan pada bulan September-Desember 2014. Data diperoleh melalui rekam medik dan didapatkan 30 kasus masuk dalam kriteria penelitian. Keseluruhan hasil penelitian didapatkan PSD lebih banyak pada penderita laki-laki 27 orang (90%). Golongan umur terbanyak pada anak-anak (<12 tahun) 11 orang (37%). Lokasi PSD terbanyak pada temporal 9 kasus (30%).Kata kunci: perdarahan subdural, computed tomography scan